Detection of Herpes simplex virus, Cytomegalovirus and Epstein-Barr virus in Ulcerative Colitis patients by PCR method - Mehrabani Khasraghi, Sahar; Ameli, Mitra; Khalily, Farzad (Archives of Advances in Biosciences, 2015)
Ulcerative Colitis (UC) is one type of inflammatory bowel disease (IBD). Herpes viruses have been suggested as possible etiological agents of UC and Crohn’s disease (CD). The aim of this study was to investigate the prevalence of Herpes Simplex virus (HSV), Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) in patients with UC in comparison with healthy subjects by using PCR technique. In this analytical case-control study, five patients with UC and thirty healthy patients as controls were selected. Sampling was performed by endoscopic biopsy operation. Biopsy specimens were frozen under sterile conditions at -20˚C until analysis. After DNA extraction, analysis of PCR to detect HSV, CMV and EBV DNA in tissue samples was performed. Statistical analysis was performed with the χ2 test. We observed HSV DNA in 80% of UC samples (4 of 5) and 10% from the normal control group (3 of 30). CMV DNA was found in 80% of UC samples (4 of 5) and 30% from the normal control group (9 of 30). Also, EBV DNA was found in 60% of UC samples (3 of 5) and 36.7% from the normal control group (11 of 30). Statistical analysis showed a significant association between the prevalence of HSV and CMV and the incidence of UC compared with the control group. The results of the present study has shown UC patients have a predisposition to HSV and CMV infections as compared to healthy individuals. Also, the results demonstrate a lack of direct molecular evidence to support an association between HSV and CMV with UC.